A Painless Thoracic Aortic Dissection - Youssef Mahmoud; Tamer Shalaby; Nazia Rashid (European Journal of Case Reports in Internal Medicine, 2016)
Thoracic aortic dissection (TAD) has a very high mortality rate and is often missed due to the atypical presentation of patients. We present a case of a man with chronic hypertension, atrial fibrillation (AF) (on regular warfarin) and a previous endovascular aneurysm repair (EVAR), who presented with dyspepsia and was incidentally found to have a ruptured distal thoracic aneurysm on imaging with no obvious clinical signs on examination, nor abnormalities on admission chest x-ray (CXR).